Penerapan Model PjBL Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMP - Savitri, Dwi Ananda; Sari, Eka Fitri Puspa; Retta, Allen Marga (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to examine the effectiveness of the Project Based Learning (PjBL) model in improving the problem-solving skills of class VIII.4 students at SMP Negeri 45 Palembang with a focus on the topic of data presentation. The research sample consisted of 29 students; the method used was experimental design with a One-Group Pretest-Posttest approach. Data collection was carried out through pretest and posttest which contained problem solving questions. The research results showed that there was a significant increase in students' problem-solving abilities after implementing the PjBL model, with a value of Sig. (2-tailed) of 0.05. N-gain analysis also categorizes student skill improvement in the medium category. These findings indicate that the PjBL model can be an effective alternative for improving critical thinking skills.